Impact of Cognitive Function and Cancer Coping on Quality of Life among Women with Post-chemotherapy Breast Cancer - Yoon Jung Kim; Sook Jung Kang (Korean Society of Women Health Nursing, 2016)
PURPOSE: This study was done to identify effects of cognitive function and cancer coping on quality of life among women with breast cancer treated with antineoplastic agents. METHODS: The study was correlational research and participants were 145 women with breast cancer who had received antineoplastic agents. Data were collected from October to November, 2015 via online replies. Cognitive function was measured with the Functional Assessment of Cancer Therapy-Cognitive Function Version-3 (FACT-Cog), cancer coping, with the Korean Cancer Coping Questionnaire (K-CCQ), and quality of life with the Functional Assessment of Cancer Therapy-Breast Version-4 (FACT-B). Data were analyzed using descriptive statistics, t-test, ANOVA, Scheffé test, ANCOVA, Bonferroni test, partial correlation coefficient, and hierarchical multiple regression with SPSS 21. RESULTS: Cognitive functions, total individual coping, and interpersonal coping explained 42% of quality of life. Cognitive function (β=.35, p<.001) was the best predictor of quality of life, followed by total individual coping (β=.34, p<.001), and interpersonal coping (β=.26, p<.001). CONCLUSION: Results indicate that cognitive function and cancer coping are meaningful factors for quality of life among breast cancer survivors. Therefore when developing intervention programs for these women, content on cognitive function and coping skills as well as coping resources should be included.